2016
DOI: 10.5194/hess-20-1085-2016
|View full text |Cite
|
Sign up to set email alerts
|

Reviving the Ganges Water Machine: potential

Abstract: Abstract. The Ganges River basin faces severe water challenges related to a mismatch between supply and demand. Although the basin has abundant surface water and groundwater resources, the seasonal monsoon causes a mismatch between supply and demand as well as flooding. Water availability and flood potential is high during the 3-4 months (June-September) of the monsoon season. Yet, the highest demands occur during the 8-9 months (October-May) of the non-monsoon period. Addressing this mismatch, which is likely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…This demonstrates the role that surface water infiltration could play in maintaining irrigation water supply through managed aquifer recharge, a process explored or practiced in many regions – for example, India, the United States and historically as a small‐scale intervention in pre‐Inca infiltration structures in the tropical Andes (Shah, ; Massuel et al, ; Scanlon et al, ; Ochoa‐Tocachi et al, ). Managing aquifer recharge and discharge is a concept central to the Ganges Water Machine (GWM) (Revelle and Lakshminarayana, ; Khan et al, ; Amarasinghe et al, ). The GWM involves drawing down groundwater levels through increased pumping prior to the onset of the monsoon when aquifers will be recharged.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the role that surface water infiltration could play in maintaining irrigation water supply through managed aquifer recharge, a process explored or practiced in many regions – for example, India, the United States and historically as a small‐scale intervention in pre‐Inca infiltration structures in the tropical Andes (Shah, ; Massuel et al, ; Scanlon et al, ; Ochoa‐Tocachi et al, ). Managing aquifer recharge and discharge is a concept central to the Ganges Water Machine (GWM) (Revelle and Lakshminarayana, ; Khan et al, ; Amarasinghe et al, ). The GWM involves drawing down groundwater levels through increased pumping prior to the onset of the monsoon when aquifers will be recharged.…”
Section: Discussionmentioning
confidence: 99%
“…The groundwater pumped is assumed to be consumptive use for ET and hence is lost from the system. In Amarasinghe et al (2016), scenario 2 of unmet agriculture water demand indicated that the agricultural areas in the Ramganga sub-basin could be increased by another 160 000 ha. Thus for this analysis we only consider scenario 2 (from Amarasinghe et al, 2016) of the unmet agriculture water demand.…”
Section: Effect Of Enhanced Groundwater Recharge and Increased Pumpinmentioning
confidence: 99%
“…In Amarasinghe et al (2016), scenario 2 of unmet agriculture water demand indicated that the agricultural areas in the Ramganga sub-basin could be increased by another 160 000 ha. Thus for this analysis we only consider scenario 2 (from Amarasinghe et al, 2016) of the unmet agriculture water demand. We assume that the additional agriculture area will be wheat, as this crop is predominantly grown during the period of November to March.…”
Section: Effect Of Enhanced Groundwater Recharge and Increased Pumpinmentioning
confidence: 99%
See 2 more Smart Citations